Both alpha(1)- and beta(1)-adrenoceptors in the bed nucleus of the stria terminalis are involved in the expression of conditioned contextual fear - Hott, Sara C.; Gomes, Felipe V.; Fabri, Denise R. S.; Reis, Daniel G.; Crestani, Carlos Cesar [UNESP]; Correa, Fernando M. A.; Resstel, Leonardo B. M. (Wiley-Blackwell, 2012)
BACKGROUND and PURPOSE The bed nucleus of the stria terminalis (BNST) is a limbic structure that is involved in the expression of conditioned contextual fear. Among the numerous neural inputs to the BNST, noradrenergic synaptic terminals are prominent and some evidence suggests an activation of this noradrenergic neurotransmission in the BNST during aversive situations. Here, we have investigated the involvement of the BNST noradrenergic system in the modulation of behavioural and autonomic responses induced by conditioned contextual fear in rats. EXPERIMENTAL APPROACH Male Wistar rats with cannulae bilaterally implanted into the BNST were submitted to a 10 min conditioning session (6 footshocks, 1.5 ma/ 3 s). Twenty-four hours later freezing and autonomic responses (mean arterial pressure, heart rate and cutaneous temperature) to the conditioning box were measured for 10 min. The adrenoceptor antagonists were administered 10 min before the re-exposure to the aversive context. KEY RESULTS L-propranolol, a non-selective beta-adrenoceptor antagonist, and phentolamine, a non-selective a-adrenoceptor antagonist, reduced both freezing and autonomic responses induced by aversive context. Similar results were observed with CGP20712, a selective beta 1-adrenoceptor antagonist, and WB4101, a selective a1-antagonist, but not with ICI118,551, a selective beta 2-adrenoceptor antagonist or RX821002, a selective a2-antagonist. CONCLUSIONS and IMPLICATIONS These findings support the idea that noradrenergic neurotransmission in the BNST via a1- and beta 1-adrenoceptors is involved in the expression of conditioned contextual fear.
Keywords: noradrenergic system; adrenoceptor antagonists; autonomic responses; cardiovascular system; conditioned emotional responses